Data warehouse and its impact on agile decision-making at Best Cable Peru - Perez Quispe, Cesar Alcides (2024)
Business intelligence provides significant assistance in decision-making by offering a comprehensive overview of the business and its workflow, presenting various alternatives to decision-makers. The research aimed to streamline decision-making within the company through the implementation of a Data Warehouse. The Kimball methodology was employed in the process, utilizing Atoti Apache Airflow and PowerBI software, which were fed with transactional data stored in a MariaDB database. Statistical analysis was conducted using R software within the RStudio environment. The study population consisted of 5 employees for the user satisfaction indicator, employing a convenience non-probabilistic sampling method, while for the indicators of report generation time and costs, the population comprised 360 management reports, sampled using a simple probabilistic method, resulting in a sample of 186 management reports. The results indicated a 94.37% reduction in the time required for report generation, a 94.72% decrease in associated costs, and a 72.36% increase in user satisfaction level. Upon analysis, it was determined that the implementation of business intelligence significantly improved decision-making agility within the company, confirming its effectiveness.